БНХАУ-аас Монгол Улсад хөрөнгө оруулагчдын Зунхуа нийгэмлэгийн тэргүүн Лю Венькегийн хэлсэн үг (Journal of International Studies, 2014)
English title: Remarks by Liu Wenke, Head of the Zunhua Association of the People Republic of China’s investors in Mongolia